Analyzing and Explaining the Concept and Domain of Prayer - jamshid sadri (پژوهش نامه معارف قرآنی, 2011)
Prayer has constantly cast a shadow on human life throughout the history and has enjoyed such extensiveness that involves both the believers and the pagans. lnvcstigation and analysis of its common and different aspects against words such as worship, call, question, and invitation an<l explanation of its relationship with affairs such as fate and destiny, innate nature and authority of human, and depicting its position in the system of existence result in the proper function and timely expectation being revealed in the system of human life .This study sets out to investigate the terminological and literal meaning of prayer and examine its relationship with words such as invitation, call, innate nature, and worship. Finally, it has considered the domain of prayer as the main cause of the cause chain